Models of management based on transformational leadership to improve the quality of university processes - Chafloque Céspedes, Raquel (2019)
The main objective of this research was to propose a management model based on transformational leadership to improve the quality of university processes. It was attended by all managers (10 participants), administrative workers (7 participants), teachers (164 teachers) and students (340 participants) who belong to the different Professional Schools of the Private University Filial Chiclayo. A quasi-experimental study was made. The results obtained show that after having analyzed the components of the university process and having made a 360 ° assessment in relation to the leadership of the managers, it is necessary to apply a management model with a certain type of leadership, which according to the theory It should be based on the type of transformational leadership. This type of management model has contributed to improving the quality of the processes of the aforementioned university.